New evaluation method for the curing degree of rubber and its nanocomposites using ATR-FTIR spectroscopy - Shun Muroga (Elsevier, 2021)
A nondestructive method of evaluating the curing degree (crosslinking density) of cured rubbers and their nanocomposites based on attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy was proposed and applied to fluorine-based rubber (FKM), in which triallyl-isocyanurate (TAIC) was employed as a curing agent. ATR-FTIR spectroscopy demonstrated that the CO band in TAIC at 1699 cm−1 decreased in intensity and broadened as the curing reaction progressed. A calibration model relating the crosslinking density in the FKM with the full width at half maximum (FWHM) of the band of the CO bond was developed. The model showed good applicability to both FKM and FKM nanocomposites with various nanofillers, including single- and multi-walled carbon nanotubes (CNTs), carbon black and silica particles. Interestingly, when the fillers, especially CNTs, were added to the rubber, the FWHM was more sensitive to the change in the crosslinking density than the change in the Young's modulus.